Xác định hàm lượng cadimi trong một số loài cá nước ngọt bằng phương pháp ICP-OES - Thắng, Nguyễn Quốc; Tán, Lê Văn; Kim Phượng, Nguyễn Thị (Vietnam Journal of Chemistry, 2016)
Analyses of cadmium concentrations in freshwater fishes were performed using ICP-OES. The emission line, source power, gas flow rate, volume of sample and amount of Cd were optimized. The effects of several foreign ions (Na, K, Ca, Mg, Al, Fe) were also investigated. Linear range was from 2 µg/L to 200 mg/L and linear regression was y = 1864.9x + 44.675, with correlation coefficient 0.9999. The limit of detection and limit of quantification were 0.52 and 1.73 µg/L, respectively. Recovery yield of Cd in the spiked Oreochromis sp. samples was almost 94.4 %. Concentrations of Cd in fish samples ranged from 22.7±2.9 to 28.6±3.1 µg.kg-1 and lower than permitted level set by Ministry of Health of Vietnam. Keywords. Cadmium, ICP-OES, freshwater.